Parodie Musings on Futurism and Amore in Oliverio Girondo's Espantapájaros (al alcance de todos). - Patricia Montilla (Studies in 20th & 21st Century Literature, 2005)
The Argentine poet Oliverio Girondo (1891-1967) was one of the leading figures of the Spanish American avant-garde. Appearing in 1932 approximately two decades after the rise of Futurism, Girondo's third collection of poetry, Espantapájaros (al alcance de todos), mocks the already clichéd literary conventions promulgated by the avant-garde. Many of the book's poems parody the principles outlined in the founding "Manifesto of Futurism" (1909) and in F. T. Marinetti's subsequent writings. This study closely examines the poems in Espantapájaros that play on Futurism's assault on amore and sentimentality, its scorn for woman, its promotion of sex as a sole means of reproduction, and its glorification of danger and violence. It also analyzes how Girondo adapts the poetic techniques outlined in Marinetti's "Technical Manifesto of Futurist Literature" (1912) and incorporates, at times humorously, Futurist iconography of man and machine and of bodies and matter in motion. Girondo's poems question Futurist views on love while demonstrating that although once jolting and rebellious, they were quickly imitated and eventually absorbed into the literary canon. Unlike the Futurists, Girondo does not advocate a clean slate from which to create new art. Instead, the poems of Espantapájaros convey continuity through the use of parody, allowing Girondo to construct a link between the past and present and to challenge Futurist ideologies and poetics while simultaneously composing new poetry.
Keywords: Argentine poetry; Oliverio Girondo; Spanish American avant-garde; Espantapájaros (el alcance de todos); manifesto of futurism; F.T. Marinetti; futuristic iconography; machine; past; present; futurist ideology